Skeletal muscle degeneration and regeneration after injection of bothropstoxin-II, a phospholipase A2 isolated from the venom of the snake Bothrops jararacussu - Gutiérrez, J. M.; Núñez, J.; Cintra, A. C. O.; Homsi-Brandeburgo, M. I. [UNESP]; Giglio, J. R. (Academic Press Inc. Jnl-comp Subscriptions, 1991)
A myotoxic phospholipase A2, named bothropstoxin II (BthTX-II), was isolated from the venom of the South American snake Bothrops jararacussu and the pathogenesis of myonecrosis induced by this toxin was studied in mice. BthTX-II induced a rapid increase in plasma creatine kinase levels. Histological and ultrastructural observations demonstrate that this toxin affects muscle fibers by first disrupting the integrity of plasma membrane, as delta lesions were the earliest morphological alteration and since the plasma membrane was interrupted or absent in many portions. In agreement with this hypothesis, BthTX-II released peroxidase entrapped in negatively charged multilamellar liposomes and behaved as an amphiphilic protein in charge shift electrophoresis, an indication that its mechanism of action might be based on the interaction and disorganization of plasma membrane phospholipids. Membrane damage was followed by a complex series of morphological alterations in intracellular structures, most of which are probably related to an increase in cytosolic calcium levels. Myofilaments became hypercontracted into dense clumps which alternated with cellular spaces devoid of myofibrillar material. Later on, myofilaments changed to a hyaline appearance with a more uniform distribution. Mitochondria were drastically affected, showing high amplitude swelling, vesiculation of cristae, formation of flocculent densities, and membrane disruption. By 24 hr, abundant polymorphonuclear leucocytes and macrophages were observed in the interstitial space as well as inside necrotic fibers. Muscle regeneration proceeded normally, as abundant myotubes and regenerating myofibers were observed 7 days after BthTX-II injection. By 28 days regenerating fibers had a diameter similar to that of adult muscle fibers, although they presented two distinctive features: central location of nuclei and some fiber splitting. This good regenerative response may be explained by the observation that BthTX-II does not affect blood vessels, nerves, or basal laminae. © 1991.
Keywords: Batroxobin; Phospholipase a2; Animal model; Animal tissue; Cell degeneration; Cell regeneration; Histology; Myofilament; Nonhuman; Priority journal; Skeletal muscle; Snake; Ultrastructure; Animal; Cell Membrane; Creatine Kinase; Mice; Microfilaments; Microscopy, Electron; Mitochondria, Muscle; Muscles; Myofibrils; Necrosis; Peroxidase; Phospholipases A; Regeneration; Support, Non-U.S. Gov't; Animalia; Bothrops jararacussu; Lamiinae; Serpentes